Linkages and Vertical Integration in the Chinese Economy - Heimler, Alberto (The Review of Economics and Statistics, 1991)
The original concept of vertical integration can be applied only to the analysis of the relationship between final demand and gross output, but is unsuitable for most of supply-oriented studies, where what matters are the interindustry relations. For example, vertical integration of an industrial district with the rest of the economy cannot be measured with the traditional technique and should be accounted for by a different measure that considers the direct and indirect demand derived from the whole gross output of the district. In such a way it is possible to measure the expansionary potential that any industry has on any other one, constructing an index of vertical integration. These concepts are then applied to the input-output table of a developing country like China and they provide some understanding of the routes development strategies have to follow. Copyright 1991 by MIT Press.